On the application of multi-dimensional laplace decomposition method for solving singular fractional pseudo-hyperbolic equations - Eltayeb, Hassan; Kılıçman, Adem; Bachar, Imed (MDPI AG, 2022)
In this work, the exact and approximate solution for generalized linear, nonlinear, and coupled systems of fractional singular M-dimensional pseudo-hyperbolic equations are examined by using the multi-dimensional Laplace Adomian decomposition method (M-DLADM). In particular, some two-dimensional illustrative examples are provided to confirm the efficiency and accuracy of the present method.